Perkembangan Fisik Pada Masa Kanak Pertengahan - Fauziah Nasution; Adinda Hariana Safitri; Cici Ramadhani Putri; Hikmah Chairunnisa (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
During childhood, the development of a child involves several key aspects. Firstly, the physical development aspect encompasses the skeletal and muscular systems, as well as the development of motor skills. Secondly, health and safety become important focuses by providing adequate physical exercise to meet national targets and prevent children's inactivity. The processing of information and intelligence in cognitive development emphasizes repetition, organization, comparison, and the emergence of information. The division of intelligence into emotional and spiritual intelligence provides an additional dimension to understanding child development. Piaget's approach, particularly the concrete operational stage, describes a phase in which children use operations and logical reasoning in concrete situations. Lastly, in cognitive development, language becomes an important tool for communication, both in oral and sign forms.